Application of strategies such as monitoring and teachers movement to improve the classroom management when performing an english lesson. - Jara Pinto, María Esther (Machala : Universidad Técnica de Machala, 2016)
The present research is focused on the exploration and identification of suitable strategies used to improve the classroom managing, which is leaded by the teacher. the right classroom managing increases to the maximum level the learning opportunities in the students; this is why the importance of the use of strategies plays an important role in the educative process. among the mentioned strategies, we have the teacher monitoring, which executes supervision, organization and enhancing of the instruction, it also allows a better discipline control in the classroom. the teacher must be prepared to face the educative environment, because it is a big challenge where the teacher will show his abilities, the main job is to educate his students, and his management must be focused on the challenge of sharing his knowledge with them.teacher dynamic must be significant in his performance, monitoring the classroom is a continuous process that joins the professional practicing, where observation, feedback, debate, and critical-reflexive and creative analysis take place over his performance in the classroom. its objective is to achieve effectiveness in the role of the teacher in a way to improve the teaching-learning process quality. education nowadays needs qualified trainers, they have to be capable to cope in its context, they also have to be multidisciplinary and be able to satisfy the needs required by their students. training emerges like a tool that not only transfers the legacy for current and future generations, also it is the environment whereby we must instill and arouse curiosity.
Keywords: STRATEGY; MANAGEMENT; EDUCATIVE PROCESS; TEACHER MONITORING; ABILITIE; TEACHING LEARNING; EDUCATION